Pengaruh Self Assessment System dan Pemeriksaan Pajak Terhadap Penerimaan Pajak Penghasilan - Tito Marta Sugema Dasuki (Journal of Innovation in Management, Accounting and Business, 2022)
The optimal realization of income tax receipts at Kuningan region often can’t reach it’s target, so it is necessary to know the cause. There is a gap between the revenue target and tax potential This research was conducted in the KPP Pratama Kuningan. The amount of the tax officer who became the sample of this study is the tax officers from 70 KPP Pratama Kuningan with a sampling of saturated samples. The methods used in this study using this type of quantitative research. Whi le the analysis of the data by using the analysis of the coefficient of determination and test hypotheses. The results of this research show that self assessment system and examination of tax effect to income tax receipts and examination of tax doesn’t effect income tax receipts. While the simultaneous self assessment system and examination of tax proved effected income tax receipts.